SIFAT FISIK EDIBLE FILM KARAGENAN RUMPUT LAUT Eucheuma cottonii - Corputty, Anna M.; Wenno, Max R.; Lewerissa, Sherly (Pattimura University, 2025)
Edible film is an alternative packaging that can be applied to food because it is biodegradable so it is environmentally friendly, made from materials that are safe for health. The aim of this research is to determine and determine the concentration of carrageenan from Euchema cottonii seaweed which produces edible film with the best physical properties. In making edible film there are two carrageenan concentration treatments (2.5% and 3%). The method used in this research is an experimental method using two plasticizers (glycerol and sorbitol). The parameters analyzed are thickness, solubility and water vapor transmission rate (WVTR). The results of the research show that the best physical properties of edible film are: Thickness of the glycerol plasticizer with a carrageenan concentration of 2.5% with a value of 0.071 mm, solubility in the 3% concentration of the glycerol plasticizer with a value of 98.57%, WVTR for the sorbitol plasticizer with a carrageenan concentration of 3% with value 34.153 g/m2. So the results obtained show that both the concentration of carrageenan and the plasticizer have an effect on the physical and mechanical properties of the edible film produced.